The Role of Science Literacy in Improving the Quality of Physics Learning at High School Level: A Literature Review - Salsabila, Tasya; Siringoringo, Intan Mariani; Sipahutar, Sriyulina; Kasih, Joy Chatrine Okta; Hutabarat, Nurviati; Tambunan, Sentia Erlianti; Panggabean, Deo Demonta (Pusat Studi Bahasa dan Publikasi Ilmiah, 2025)
Scientific literacy is an essential competence in physics learning at the high school level because it encourages students to understand scientific concepts and apply them in real life. This study aims to examine the role of scientific literacy in improving the quality of physics learning through a literature review of various credible sources. The method used is a systematic literature review of ten scientific articles published between 2020 and 2024. The articles were analyzed to identify learning approaches, media, and strategies that contribute to enhancing students’ scientific literacy. The findings show that learning models such as problem-based learning, discovery learning, and case-based learning, along with the use of interactive digital media such as contextual videos and PhET simulations, are effective in fostering students' scientific literacy. The novelty of this review lies in the synthesis of findings from various studies that reinforce the importance of integrating scientific literacy in 21st-century contextual physics learning. The implication of this review is the need for physics teachers to design learning activities that not only focus on cognitive aspects but also cultivate critical and applicable scientific understanding in real-life contexts.